Induction sintering of silver nanoparticle inks on polyimide substrates - Tan, Hong Wei (2020)
Additive manufacturing for electronics is one of the world's fastest growing technologies in recent years. This new and upcoming technology has facilitated many innovative applications and high commercialization of metallic nanoparticle inks. A robust and novel induction sintering technique is proposed to solve the major challenges faced by the current existing sintering techniques in sintering metallic nanoparticle inks. The induction sintering process is a noncontact selective sintering process, in which only electrically conductive presintered printed patterns are heated up by alternating electromagnetic field through eddy current losses. It is also more energy-efficient and effective as compared to thermal sintering since the induction sintering process only heats the electrically conductive printed patterns rather than the entire substrate. The electrical resistivity of the induction-sintered printed pattern is measured to be 1.98 × 10−8 Ω m, which is ≈81% bulk conductivity of silver. This research breakthrough hence has the potential to overcome the challenges faced in additive manufacturing for electronics, in which printed patterns with high electrical conductivity can be fabricated on flexible substrates.